Forensic psychology : (John Wiley & Sons, 2007)
Forensic Psychology: Emerging Topics and Expanding Roles is designed to present the current state of the field, in terms of law, ethics, research and practice. Reflecting the efforts of almost 50 expert contributors, this comprehensive reference provides a basis for conducting forensic mental health assessments consistent with the state of the field as it currently exists and the standard of care that is emerging.